Living with hepatitis C: a phenomenological study. Issue 3 (9th May 2014) - Hill, Rebekah; Pfeil, Michael; Moore, Jenny; Richardson, Barbara
<x xml:space="preserve">Abstract</x> Aims and objectives To explore the experience of adults living with hepatitis C over time. Background Hepatitis C virus is a growing problem affecting thousands of people worldwide. The majority of individuals infected develop chronic liver disease, but treatment is not always successful, leaving many to live with the virus indefinitely. Experiences of living with hepatitis C are poorly understood yet essential to meet the needs of an increasing number of affected people. Design A qualitative study using a descriptive phenomenological methodology. Methods Unstructured interviews were conducted with 23 hepatitis C‐positive individuals in the East of England; participants were interviewed twice within a year. Results Data analysis revealed six themes of the experience of living with hepatitis C: hepatitis C and self; hepatitis C, self and others; self and handling hepatitis C; self and handling hepatitis C treatment issues; living with the consequences of hepatitis C; self, hepatitis C and thoughts of the future. Conclusions Diagnosis of hepatitis C can disrupt people's sense of identity and trigger a life transition. A complex range of factors create uncertainty for people living with hepatitis C. Many struggle to make a healthy transition to life with the condition, instead living in a state of sustained uncertainty. Relevance to clinical practice Nurses working within a chronic care framework of ongoing advice and support can improve experiences for those living with hepatitis C. Practice aimed at reducing both the disruptive effect of the diagnosis and the uncertainties it creates can help facilitate a transition to life with the disease.